Sintesis polianilin (PANi) dengan metode polimerisasi interfasial sebagai bahan dasar pembuatan sensor gas amonia (NH3) - M Aras, Neny Rasnyanti; Irwan, Muh (Jurnal Teknik Mesin Indonesia, 2024)
One of the main components in IoT-based devices is sensors. Polyaniline is a conductive polymer that has great potential to be developed as an active layer for chemical sensors because it has high sensitivity, is easy to synthesize and its electrical conductivity can be adjusted. This study aims to synthesize and characterize polyaniline using the interfacial polymerization method. In this study, polyaniline was synthesized by varying the aniline concentration of 2, 3, and 5 M, then its functional groups were characterized using FTIR and its conductivity and sensitivity were measured with an LCR meter. The result shows that polyaniline is in the form of emeraldine salt which is characterized by the formation of absorption bands at concentrations of 2, 3, and 5 M, respectively, 1,141.86 cm-1, 1,139 cm-1 and 1,139.93 cm-1. The highest conductivity was obtained at a concentration of 2 M, namely 4.9x10-5 and a sensitivity of 82.8% for an ammonia concentration of 100 ppm. So it can be concluded that the polyaniline obtained is a form of semiconducting emeraldine salt.